Mixed-cation driven magnetic interaction of interstitial electrons for ferrimagnetic two-dimensional electride - Seung Yong Lee; Joonho Bang; Hyun Yong Song; Byung Il Yoo; Yeongkwan Kim; Kimoon Lee; Dinesh Thapa; Seong-Gon Kim; Sung Wng Kim (npj Quantum Materials, 2021)
Abstract Magnetism of pure electrons is fundamental for understanding diverse magnetic phenomena in condensed matters but has not been fully investigated in experiments due to the lack of a tractable model system. Such an exotic material necessitates an exclusive magnetic interaction of electrons being devoid of orbital and lattice degrees of freedom. Here, we report the two-dimensional mixed-cation [YGdC]2+∙2e− electride, showing ferrimagnetic nature from the direct exchange interaction of magnetic interstitial electrons in interlayer space. We identify that magnetic interstitial electrons are periodically localized in octahedral and tetrahedral cavities between 2D cationic Y2−x Gd x arrays. The mixed configuration of non-magnetic and magnetic cations in cavities induces divergent spin states and interactions of magnetic interstitial electrons, in which their direct exchange interaction overwhelms the interactions with magnetic cations, triggering the ferrimagnetic spin-alignment. This discovery facilitates further exploration of magnetic electrides and nurtures the study of two-dimensional magnetism of layered crystals and electron phases.